AGE AND PETROGENESIS OF THE JIANFENGLING GRANITE AND ITS RELATIONSHIP TO METALLOGENESIS OF THE BAOLUN GOLD DEPOSIT, HAINAN ISLAND - Xie C.F.; Zhu J.C.; Zhang Y.M.; Fu T.A.; Li Z.H.; Ding S.J.; Chen M.L.; Fu Y.R. (My University, 2006)
The Jianfengling composite batholith is chiefly composed of the Jianfengling superunit with medium-coarse grained porphyritic, fine-grained porphyritic, coarse-medium grained and fine-grained biotite syenogranites. These rocks are weakly peraluminous-metaluminous, with high alkalinity ratios (AR) and belonging to the alkaline series. In general they are enriched in Si, K, Rb, Cs, Th, U, Pb, Zr, Hf, Y, strongly depleted in Ba, Sr, P, Ti and moderately depleted in Nb, Ta. The early unit has high REE contents and the later units have distinctly low REE contents. It displays remarkable differentiation between LREE and HREE, with (La/Yb)N = 8.29 ~ 30.36, medium to strong depletion of Eu (δEu = 0.43 ~ 0.05), high (87Sr/86Sr)i values (0.71658 ~ 0.71703), moderately old Nd model ages (T2DM = 1639 ~ 1709Ma), and moderately low εNd (t) values (-7.59 ~ -8.46). A zircon SHRIMP U-Pb dating yields a crystallization age of 249 ± 5Ma for the Jianfengling superunit. This study indicates that the Jianfengling superunit, which belongs to a genesis type between S-type and aluminous A-type granite, and is similar to high heat production (HHP) granite, was produced at a temperature of 770 ~ 790°C and a pressure of (10 ~ 12.5) 108 Pa (corresponding to a depth of 34 ~ 42km) by partial melting of crust metagreywackes or metapsammites enriched by mantle-derived fluid, which was in turn caused by Early Triassic lithospheric delamination and upwelling of a hot asthenosphere under a post-orogenic environment. The intrusive melts experienced strong crystallization fractionation. The age when temperature of the middle of the batholith fell at about 300°C is 221 ~ 209Ma, which is close to the mineralization age (220 ~ 200Ma) of the Baolun Au deposit located in exocontact of the batholith, and is about 30 ~ 40Ma latter than the crystallization age. This long-lived high-medium temperature setting was very helpful to the formation of hydrothermal convective circulation system that result in ore formation. But the granite was mainly acted as a source of heat energy for the metallogenesis of Au, rather than directly providing fluid and ore-forming materials. Therefore, we suggest to classify the Baolun gold deposit as "hydrothermal deposit associated with HHP granite".
Keywords: BAOLUN GOLD DEPOSIT; HAINAN; HIGH HEAT PRODUCTION GRANITE; INDOSINIAN; JIANFENGLING GRANITE; POST-OROGENIC; SHRIMP U-PB DATING; Мезозой::Триасовая; Mesozoic::Triassic